Development, Identification, and Genetic Analysis of a Quantitative Dwarfing Somatic Variation Line in Wheat. Issue 3 (1st May 2013) - Wang, Ke; Wang, Shunli; Zhou, Xiaohong; Lin, Zhishan; Li, Jiarui; Du, Lipu; Tang, Yimiao; Xu, Huijun; Yan, Yueming; Ye, Xingguo
ABSTRACT: Dwarfing germplasms are crucial to the development of wheat ( Triticum aestivum L.) varieties with ideal plant height and combinations of agronomic traits. A novel dwarfing wheat line, AS34, was developed in this study by somatic variation. This new wheat germplasm was confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis, two‐dimensional gel electrophoresis, genomic in situ hybridization, and genomic scanning with 44 simple sequence repeat (SSR) markers, and our analysis showed that AS34 was clearly derived from the somatic variation of Yumai66 (YM66), its tissue culture parent, but not from natural hybridization. Molecular tests using known primers specific to Rht8 and Rht ‐ B1b genes indicated that AS34 and its parent contained Rht8 but not Rht ‐ B1b in their genomes, which was not consistent with previous reports. Similar to YM66, AS34 was sensitive to gibberellic acid, and this characteristic might be induced only by Rht8 or by Rht8 and the new dwarfing genes simultaneously. Genetic analysis revealed that the new dwarfing trait in AS34 was controlled by multiple quantitative genes, and data from the F2 population yielded no key quantitative trait locus. According to the results of genomic scanning for different SSR markers, some of the new dwarfing genes in AS34 might be located on chromosome 4B. The new dwarfing material had positive effects on the agronomic traits related to grain yield in F2 populations, particularly the variation range in plant height. This dwarfing resource will be potentially used in wheat breeding for the development of new wheat varieties with available agronomic traits.